Gene Transfection and Expression of Transforming Growth Factor-β1 in Nonobese Diabetic Mouse Islets Protects β-Cells in Syngeneic Islet Grafts from Autoimmune Destruction - Wilma L. Suarez-Pinzon; Yvonne Marcoux; Aziz Ghahary; Alex Rabinovitch M.D. (Cell Transplantation, 2002)
Nonobese diabetic (NOD) mice develop diabetes and destroy syngeneic islet grafts through an autoimmune response. Because transforming growth factor (TGF)-β1 downregulates immune responses, we tested whether overexpression of TGF-β1 by gene transfection of NOD mouse islets could protect β-cells in islet grafts from autoimmune destruction. NOD mouse islet cells were transfected with an adenoviral DNA expression vector encoding porcine latent TGF-β1 (Ad TGF- β1) or the adenoviral vector alone (control Ad vector). The frequency of total islet cells expressing TGF-1 protein was increased from 12±1% in control Ad vector-transfected cells to 89 ± 4% in Ad TGF-β1-transfected islet cells, and the frequency of β-cells that expressed TGF-β1 was increased from 12 ± 1% to 60 ± 7%. Also, secretion of TGF-β1 was significantly increased in islets that overexpressed TGF-β1. Ad TGF-β1-transfected NOD mouse islets that overexpressed TGF-β1 prevented diabetes recurrence after transplantation into diabetic NOD mice for a median of 22 days compared with only 7 days for control Ad vector-transfected islets (p = 0.001). Immunohistochemical examination of the islet grafts revealed significantly more TGF-β1+ cells and insulin+ cells and significantly fewer CD45+ leukocytes in Ad TGF-β1-transfected islet grafts. Also, islet β-cell apoptosis was significantly decreased whereas apoptosis of graft-infiltrating leukocytes was significantly increased in Ad TGF-β1-transfected islet grafts. These observations demonstrate that overexpression of TGF-β1, by gene transfection of NOD mouse islets, protects islet β-cells from apoptosis and autoimmune destruction and delays diabetes recurrence after islet transplantation.